2015
DOI: 10.1016/j.cognition.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Imitate or innovate? Children’s innovation is influenced by the efficacy of observed behaviour

Abstract: This study investigated the age at which children judge it futile to imitate unreliable information, in the form of a visibly ineffective demonstrated solution, and deviate to produce novel solutions ('innovations'). Children aged 4-9 years were presented with a novel puzzle box, the Multiple-Methods Box (MMB), which offered multiple innovation opportunities to extract a reward using different tools, access points and exits. 209 children were assigned to conditions in which eight social demonstrations of a rew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 57 publications
4
92
1
Order By: Relevance
“…Support for this thought comes from our finding that participants in our demo conditions were not able to go beyond the height of the demonstrated tripod and that only one participant (in the endstate-only demo condition) built a level-4-tripod. Furthermore, research on innovation in children demonstrated surprisingly low innovation rates with regard to making tools 67 or inventing strategies to retrieve more rewards from a puzzle-box 68 : Children well into their primary school years seem to struggle with inventing (better) solutions to new tasks. This might imply that groups of young children might not yet be able to show a ratchet effect as continuing limitations on their ability to innovate represents a critical bottleneck for the development of a capacity for producing culture-dependent traits [see also refs 69 and 70].…”
Section: Discussionmentioning
confidence: 99%
“…Support for this thought comes from our finding that participants in our demo conditions were not able to go beyond the height of the demonstrated tripod and that only one participant (in the endstate-only demo condition) built a level-4-tripod. Furthermore, research on innovation in children demonstrated surprisingly low innovation rates with regard to making tools 67 or inventing strategies to retrieve more rewards from a puzzle-box 68 : Children well into their primary school years seem to struggle with inventing (better) solutions to new tasks. This might imply that groups of young children might not yet be able to show a ratchet effect as continuing limitations on their ability to innovate represents a critical bottleneck for the development of a capacity for producing culture-dependent traits [see also refs 69 and 70].…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest a lack of sophistication in tool innovation in young children and a reliance on being shown task solutions by adults [86]. One possibility is that innovation requires didactic pedagogy and scaffolding from others.…”
Section: The Evolution and Ontogeny Of Innovationmentioning
confidence: 99%
“…The ontogeny of tool use is of interest because tool use characterizes all human environments, is fundamental to cumulative culture, and is learned early. Children are excellent social learners , but they find solving innovation challenges difficult asocially, especially in early childhood, with most children under age 8 failing innovation challenges .…”
Section: Do Children Who Tend To Learn Asocially Differ From Those Whmentioning
confidence: 99%